In vitro and in silico inhibition performance of choline against CYP1A2, CYP2D6 and CYP3A4. Issue 1 (5th November 2022) - Mateev, Emilio; Balkanska-Mitkova, Tony; Peikova, Lily; Dimitrova, Maria; Kondeva-Burdina, Magdalena
Abstract: Choline is an essential nutrient involved in the synthesis of acetylcholine in the cholinergic neurons. The pharmacokinetic properties of choline are well described; however, there is a lack of data about its activity toward the CYP450 superfamily of enzymes. Therefore, the aim of this study was to conduct in silico and in vitro activity assessments of choline against three major CYP450 isoforms—CYP1A2, CYP2D6, and CYP3A4. Preliminary in silico modeling was performed on a specialized DL-CYP Prediction Server to evaluate the affinity of choline toward the enzymes. The in vitro study contained specific cytochrome P450 isoform inhibitors and substrates (for CYP1A2, CYP2D6, and CYP3A4) to determine the inhibition performance of choline at five different concentrations (0.150 − 1 µmol/L). The potential interactions of choline and CYPs were displayed after molecular docking with Glide (Schrödinger). In addition, induced-fit simulations and binding free energy calculations MM/GBSA (Molecular Mechanics-Generalized Born Surface Area) were applied to predict the accessibility in each CYP isoform. The initial in silico simulations revealed that choline lacks inhibition potency against the aforementioned enzymes. The in vitro evaluations confirmed that choline possessed no effect against CYP1A2; however, at 1 µmol/L choline exerted 22% and 27% blocking capacity against CYP2D6 and CYP3A4, respectively. Furthermore, there was good correlation between the in vitro results and the complexes' free binding energy recalculations. Overall, the assessments indicated that choline is a weak CYP2D6 and CYP3A4 inhibitor. The latter results should be considered as a source of future unwanted drug–drug interactions.